Síntese de novos pirróis derivados de aminocumarinas - Brites, Nathan Pinto (2018)
In this work, the synthesis of new pyrroles derived from aminocoumarins was developed. First, the synthesis of pyrroles derived from 4-amino-2H-chromen-2-one was carried out by the Paal-Knorr and Clauson-Kaas reactions, using anhydrous cerium chloride and PTSA.H2O as catalysts. The reaction was carried out under conventional heating and microwave irradiation, using 2,5-hexanedione (1.2 equiv.) and 2,5-dimethoxy-THF (3 equiv.) in toluene and acetonitrile as solvents, respectively. A novel methodology for synthesizing pyrroles from 6-amino-2H-chromen-2-one was also explored. In this synthesis, anhydrous cerium chloride as catalyst and acetonitrile was used as solvent at reflux temperature. Finally, it was evaluated the functionalization of this class of compounds, performing the thiocyanation of selected pyrroles.